Novel Carbon-Based Magnetic Luminescent Nanocomposites for Multimodal Imaging - Liu, Fangfang; Mou, Xiaoming; Song, Jimei; Li, Qin; Liu, Jinliang (Frontiers in Chemistry, 2020)
Multifunctional nanocomposites can integrate multiple functionalities into one single nanosystem and thus have attracted extensive interest in various fields. The combination of magnetic and upconversion luminescent (UCL) nanoparticles into one single nanoplatform to construct magnetic luminescent nanoparticles is highly desirable in biomedical applications such as bio-magnetic separation, magnetic resonance imaging (MRI) and optical imaging. Here we report multifunctional nanocomposites by using a hollow carbon sphere to combine superparamagnetic Fe3O4 and upconversion nanoparticles (UCNPs) into one nanosystem. The as-prepared UCNPs/Fe3O4@h-C are endowed with near-infrared (NIR) luminescence upon 980 nm excitation and superparamagnetism. In addition, since the carbon layer can convert the absorbed light into heat with high efficiency, the nanocomposites can realize photo thermal (PT), UCL and MRI tri-mode imaging. The UCNPs/Fe3O4@h-C might be further investigated as a new theranostic agent, including being monitored with deep insight by luminescent imaging and MRI diagnosis, and simultaneously directed to cancer tumors as a photothermal therapy (PTT) agent.